2017
DOI: 10.1016/j.janxdis.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The Looming Maladaptive Style Questionnaire: Measurement invariance and relations to anxiety and depression across 10 countries

Abstract: The Looming Maladaptive Style Questionnaire (LMSQ) is a self-report measure designed to assess the looming cognitive style, a tendency to interpret threats as rapidly approaching and increasing in magnitude. To date, no systematic evaluation on the psychometric properties of the LMSQ across diverse cultural contexts has been done. In the present research, the measurement invariance of the LMSQ test scores was examined in 10 countries (N=4000). Confirmatory factor analysis suggested that a two-factor model (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 61 publications
3
6
0
1
Order By: Relevance
“…The high degree of construct compatibility is likely to be due to the highly Westernized aspect of the Singapore society that adopted many European American cultural ethos and values into its institutions while still embracing traditional Asian collectivistic principles (Luo, Hogan, & Paris, 2011). Moreover, our findings are aligned with research across the United States and Singapore in the past decade (e.g., Hong et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The high degree of construct compatibility is likely to be due to the highly Westernized aspect of the Singapore society that adopted many European American cultural ethos and values into its institutions while still embracing traditional Asian collectivistic principles (Luo, Hogan, & Paris, 2011). Moreover, our findings are aligned with research across the United States and Singapore in the past decade (e.g., Hong et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…We first tested for configural invariance (i.e., same factor structure without placing between-group constraints on any parameter estimates) by conducting CFAs in each country and gender separately (Muthén & Muthén, 2013). To test gender invariance, data were pooled across the United States and Singapore, following others (Hong et al, 2017; Taylor et al, 2007; Whisman et al, 2020). Similarly, when testing cross-cultural equivalence, data from the United States and Singapore were pooled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, emphasis on hierarchical power structures has been shown to be higher in SG than the U.S. (Wasti et al, 2007). Also, because SG has adopted some European American cultural values and is a Southeast Asian country that uses English as the common language, research has shown a high degree of measurement invariance for various psychiatric assessments (e.g., Hong, Riskind, et al, 2017;Lowe & Ang, 2016). Collectively, cross-cultural and gender measurement invariance studies facilitate adaptation of assessment and treatment to specific groups by accounting for observed similarities and differences.…”
Section: Cross-cultural and Gender Invariance Of Five Common Symptom And Cognitive Vulnerabilitymentioning
confidence: 99%
“…ciddi bir saðlýk problemi yaþama olasýlýðý) gerçekleþme ihtimalini ve hýzýný abartýlý bir þekilde algýlama eðilimi olarak tanýmlanabilir. Bu iki alt ölçek her ne kadar kendi aralarýnda yüksek korelasyona sahip olsalar da yapýlan çalýþmalar farklý mekanizmalar ve farklý kaygý bozukluklarýyla iliþkili olabileceklerine iþaret etmektedir (5,11,12). Örneðin, alanda yapýlan deneysel çalýþmalar fiziksel abartma boyutunun iþitsel uyaranlarý olduklarýndan daha yakýnda algýlamaya yol açabileceðini, aksi þekilde sosyal abartmanýn ise uyaraný daha uzak algýlama eði-limiyle iliþkili olduðunu ortaya koymuþtur (11).…”
Section: Biliþsel Abartma Tarzý Modeliunclassified